COST-BENEFIT ANALYSIS IN POLARIZED TIMES - Gould, Jonathan S (Administrative law review, 2023)
On nearly every major issue of regulatory policy and administrative law, the two parties are sharply polarized. Yet presidential administrations of both parties have used regulatory cost-benefit analysis for nearly a half-century. Why? This Article examines the political forces that have given cost-benefit analysis staying power. While much of the existing literature focuses on the incentives of a generic President, this Article places longstanding debates over cost-benefit analysis in the context of the two parties' divergent policy agendas, the rulemaking process as a whole, and other areas of administrative law. Cost-benefit analysis has persisted because presidential administrations of both parties have reasons to think that retaining the method is consistent with their regulatory policy aims. For Republican administrations, the main utility of cost-benefit analysis is that it erects hurdles to new progressive regulatory policymaking during Democratic administrations, by imposing onerous analytic requirements on regulatory agencies. This fact helps explain why Republicans have not fully abandoned the method, even though many conservative policy goals are not supported by cost-benefit analysis. Democratic administrations have also remained faithful to the method, but for very different reasons: they have discovered the method's progressive potential, especially but not exclusively on climate issues; balked at the seeming inconsistency of abandoning the method while purporting to be the party of science and technocratic governance more generally; and been hemmed in by the prospect of conservative courts striking down agency rulemakings not backed by rigorous cost-benefit analyses.